Endometriosis and Sjögren's syndrome: Bidirectional associations in population‐based 15‐year retrospective cohorts - Ma, Kevin Sheng‐Kai; Wang, Li‐Tzu; Sasamoto, Naoko; Wang, Yu‐Hsun; Wei, James Cheng‐Chung; Einarsson, Jon Ivar; Laufer, Marc R. (Acta obstetricia et gynecologica Scandinavica, 2024)
Introduction Primary Sjögren's syndrome (pSS) is a chronic autoimmune disorder affecting salivary and lacrimal glands, while endometriosis involves uterine‐like tissue growth outside the uterus, causing pelvic pain and infertility. Investigating their intricate relationship using real‐world data is crucial due to limited research on their connection. Material and Methods This population‐based cohort study included patients with endometriosis and controls without endometriosis. Propensity score matching was used to balance baseline differences in demographic and clinic characteristics between the two groups. Cox proportional hazards model were used to estimate the effect of endometriosis on the risk of new‐onset pSS over time. A symmetrical cohort study, including patients with pSS and propensity score‐matched controls without pSS, was conducted to investigate the effect of pSS on the risk of endometriosis over time. To elaborate on the mechanisms linking endometriosis and pSS, Ingenuity Pathway Analysis was performed to identify activated pathways in eutopic endometrium from patients with endometriosis and parotid tissues from patients with pSS. Results A total of 15 947 patients with endometriosis and 15 947 propensity score‐matched controls without endometriosis were included. Patients with endometriosis presented a significantly greater risk of pSS compared to non‐endometriosis controls (adjusted hazard ratio, aHR = 1.57, 95% CI = 1.29–1.91, p < 0.001). In the symmetrical cohort study, which included 4906 pSS patients and 4,906 propensity score‐matched controls without pSS, patients with pSS were found to be at a significantly higher risk of endometriosis compared to non‐pSS controls (aHR = 1.51, 95% CI = 1.12–2.04, p = 0.012). Ingenuity Pathway Analysis showed that the underlying cellular mechanisms involved autoimmune‐related pathways, including activation of dendritic cell maturation, and chronic inflammatory pathways, including the fibrosis signaling pathway. Conclusions These findings support a bidirectional association between endometriosis and pSS, which may be driven by dendritic cell maturation and fibrosis signaling pathways. The bidirectional association between endometriosis and primary Sjögren's syndrome was observed in two population‐based cohort studies. Autoimmune‐related or chronic inflammatory pathologies may drive the link. Studies are needed to investigate whether immunomodulating therapies can attenuate these risk associations.